From women’s rights to constitutional feminism: A comparative law critique - Santos-Rodríguez, Patricia (Derecho Público Iberoamericano, 2022)
The study tries to answer the question about the meaning of including women’s rights in contemporary democratic constitutions. It offers a historiographic approach that runs through the first legal recognitions of women’s rights as an essential part of the principle of equality until the current claim of their incorporation to fundamental legal texts. The transformation of women’s rights in the second half of the twentieth century is described by the influence the feminist movements, and the new constitutionalist feminism is analysed, from its anthropological roots and legal consequences.